The Simulation of Biogas Combustion in A Mild Burner - M. M. Noor; Andrew P. Wandel; Talal Yusaf (Journal of Mechanical Engineering and Sciences, 2014)
This paper discusses the design and development of moderate and intense low oxygen dilution (MILD) combustion burners, including details of the computational fluid dynamics process, step-by-step from designing the model until post-processing. A 40 mm diameter bluff-body burner was used as the flame stabilizer. The fuel nozzle was placed in the center with a diameter of 1mm and an annular air nozzle with an opening size of 1,570 mm2, and four EGR pipes were used. Non-premixed combustion with a turbulent realizable k-epsilon was used in the simulation. The fuel used is low calorific value gas (biogas). The synthetic biogas was a mixture of 60% methane and 40% carbon dioxide. The simulation was successfully achieved during the MILD regime where the ratio of maximum-to-average temperature was less than the required 23%.